Evaluasi Kapasitas Drainase Kelurahan Klasuur Kota Sorong Menggunakan EPA - SWMM - Yasin, Azalia Fajri; Pamudjianto, Agung Pamudjianto (Universitas Tanjungpura, 2023)
The purpose of this research is to evaluate the condition of existing drainage channels in the area around Jalan Pulau Batanta Kompleks. In addition, it is also to determine the capacity of existing drainage channels to rainfall with a 2-year, 5-year and 10-year plan discharge. Rainfall frequency distribution analysis is carried out using the distribution analysis method, namely the Normal Distribution Method with chi-square calculations and Kolmogorov Smirnov suitability test. Rainfall intensity is calculated using the Mononobe equation and modeling with EPA-SWMM by simulating the drainage network and calculating the flood inundation area. The existing condition of the drainage system in the complex area along Jalan Batanta Island in accommodating the maximum rainfall discharge is still often overflowing, this is obtained from the results of the EPA-SWMM analysis that the channels around Jalan R.A. Kartini overflowed the most in the return periods of 2 years, 5 years, and 10 years with the largest runoff in channel 15. From the results of the evaluation of drainage channels and networks, it is known that the cause of flooding in the area around Jalan Batanta Island Complex is the existence of drainage channels that should accommodate rainwater, due to the large amount of sedimentation, as well as garbage that reduces the capacity of other channels. All channels reviewed have a sub-drainage area of 3.18 Ha with a total length of 7544.33 meters in good condition.